2017
DOI: 10.1590/s0102-053620170120
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de linhagens e híbridos de pimentão em dois sistemas de poda no cultivo hidropônico

Abstract: RESUMO Objetivou-se avaliar dois sistemas de poda em genótipos de pimentão hidropônico visando maiores produtividade e qualidade de frutos. Foi utilizado o delineamento em blocos casualizados, três repetições e tratamentos arranjados em parcelas subdivididas. As parcelas corresponderam aos dois sistemas de poda 1-2-4-N e 1-2-4 e as subparcelas aos genótipos de pimentão. O primeiro sistema de poda consistiu em deixar uma haste seguida de duas brotações e mais duas brotações de cada uma destas hastes, de modo a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
2
0
4
Order By: Relevance
“…Mass, diameter and length of fruits as well as the bell pepper peel thickness in relation to different harvest seasons (90, 120 and 150 DAT) presented higher average values in the first and second harvests, differing from the third harvest (Table 3). This analysis of fruit quality per harvest is important, since these are determinant characteristics for classification and commercialization of bell pepper and, since Brazilian market appreciates big fruits (Santos et al, 2017). Therewith, the producer can manage the supply of bell pepper available to the market and that way it is possible to obtain better prices ETc in vegetative phase (FI) and 100% ETc in production phase (FII); RDI (II)-100% ETc in FI and 50% ETc in FII; RDI (III)-75% ETc in FI and 100% ETc in FII; RDI (IV)-100% ETc in FI and 75% ETc in FII; RDI (V)-125% ETc in FI and 75% ETc in FII; RDI(VI)-75% ETc in FI and 125% ETc in FII.…”
Section: Resultsmentioning
confidence: 99%
“…Mass, diameter and length of fruits as well as the bell pepper peel thickness in relation to different harvest seasons (90, 120 and 150 DAT) presented higher average values in the first and second harvests, differing from the third harvest (Table 3). This analysis of fruit quality per harvest is important, since these are determinant characteristics for classification and commercialization of bell pepper and, since Brazilian market appreciates big fruits (Santos et al, 2017). Therewith, the producer can manage the supply of bell pepper available to the market and that way it is possible to obtain better prices ETc in vegetative phase (FI) and 100% ETc in production phase (FII); RDI (II)-100% ETc in FI and 50% ETc in FII; RDI (III)-75% ETc in FI and 100% ETc in FII; RDI (IV)-100% ETc in FI and 75% ETc in FII; RDI (V)-125% ETc in FI and 75% ETc in FII; RDI(VI)-75% ETc in FI and 125% ETc in FII.…”
Section: Resultsmentioning
confidence: 99%
“…As well as Frizzone et al (2001), which found a thickness of the mesocarp of the bell pepper varying from 2.6 to 5.3 mm. Santos et al (2017) evaluating several bell pepper genotypes, obtained values of this between 4.17 and 7.70 mm.…”
Section: Resultsmentioning
confidence: 99%
“…O peso médio de frutos foi obtido pela soma do peso total de frutos e dividido pelo número de frutos por planta, com resultados expressos em gramas (FREITAS, 2009). Para determinar o comprimento médio de fruto foi utilizado um paquímetro digital, medindose o comprimento longitudinal do fruto, com resultados expressos em milímetros (SANTOS et al;2016).…”
Section: Foi Realizado Apenas Uma Colheita Aos 115 Dias Após O Transplantio Das Mudas Para O Campounclassified
“…Características como peso médio e comprimento de frutos são de suma importância na produção de pimentão, pois são caracteres que determinam a classificação (qualidade do produto) e favorecem a comercialização, pois geralmente o mercado consumidor brasileiro apresenta grande valorização por frutos de tamanhos grandes (SANTOS et al, 2017).…”
Section: Fontes De Variaçãounclassified